Web-based conference management system / Husnul Nisa' Rosli - Rosli, Husnul Nisa' (2010)
Nowadays, the Internet and web allows people to access and retrieve information, therefore with these advantages of the Internet, there should be a web-based system developed to help the organization in managing their conference wisely and easily. Organizing a conference can be very time consuming and difficult to manage because it is involving a lot of manpower. Therefore, conference websites is proposed to overcome the problems. The proposed system will enable the organizer to manage their conference with ease. The system will be developed using PHP programming language and Mysql database. It is hoped that the system will assist the Program Committee (PC) and administrative staff to effortlessly manage their conferences online and deliver the best experience to the authors and reviewers.